Reduced Endothelial Function in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome–Results From Open-Label Cyclophosphamide Intervention Study - Sørland, Kari; Sandvik, Miriam Kristine; Rekeland, Ingrid Gurvin; Ribu, Lis; Småstuen, Milada Cvancarova; Mella, Olav; Fluge, Øystein (Frontiers in Medicine, 2021)
Abstract Introduction Patients with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) present with a range of symptoms including post-exertional malaise (PEM), orthostatic intolerance and autonomic dysfunction. Dysfunction of the blood vessel endothelium could be an underlying biological mechanism, resulting in inability to fine-tune regulation of blood flow according to the metabolic demands of tissues. The objectives of the present study were to investigate endothelial function in ME/CFS patients compared to healthy individuals, and assess possible changes in endothelial function after intervention with IV cyclophosphamide. Methods This substudy to the open-label phase II trial “Cyclophosphamide in ME/CFS” included 40 patients with mild-moderate to severe ME/CFS according to Canadian consensus criteria, aged 18-65 years. Endothelial function was measured by Flow-mediated dilation (FMD) and Post-occlusive reactive hyperemia (PORH) at baseline and repeated after 12 months..Endothelial function at baseline was compared with two cohorts of healthy controls (N=66 and N=30) from previous studies. Changes in endothelial function after 12 months were assessed and correlated with clinical response to cyclophosphamide. Biological markers for endothelial function were measured in serum at baseline and compared with healthy controls (N=30). Results Baseline FMD was significantly reduced in patients (median FMD 5.9%, range 0.5-13.1, n=35) compared to healthy individuals (median FMD 7.7%, range 0.7-21, n=66) (p=0.005), as was PORH with patient score median 1331 p.u. (range 343-4334) versus healthy individuals 1886 p.u. (range 808-8158) (p=0.003). No significant associations were found between clinical response to cyclophosphamide intervention (reported in 55 % of patients) and changes in FMD/PORH from baseline to 12 months. Serum levels of metabolites associated with endothelial dysfunction showed no significant differences between ME/CFS patients and healthy controls. Conclusions Patients with ME/CFS had reduced endothelial function affecting both large and small vessels compared to healthy controls. Changes in endothelial function did not follow clinical responses during follow-up after cyclophosphamide IV intervention.